Competencias docentes para la detección temprana del trastorno del espectro autista en niños de preescolar - Yerovi Saltos, Martha Cecilia (2021)
In the international and national context, the importance of early detection and care of children with Autism Spectrum Disorder (ASD) has been demonstrated, however, at the preschool level, given the very nature, variability and characteristics of each case, there are still gaps that make this process in a constant challenge. In an observation carried out in the Basic School: Alegrias Infantiles, it was possible to detect the presence of limitations in the competencies of the teachers who work at the preschool level to be able to detect attend to the cases of children who attend the classrooms with possible manifestations of TEA. That is why the present work has as its General Objective………..